1989
DOI: 10.1016/s0022-5347(17)40760-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Demonstration of S Phase Cells by Antlbromobeoxyuribine Monoclonal Antibody in Human Prostate Adenocarcinoma

Abstract: Using a monoclonal antibody to bromodeoxyuridine and immunohistochemistry, we measured the incorporation of this thymidine analogue into the deoxyribonucleic acid of human prostate adenocarcinoma cells exposed in situ. Fifteen patients with prostate cancer were given an intravenous infusion of 500 mg. bromodeoxyuridine at needle biopsy to label tumor cells in the deoxyribonucleic acid synthesis phase (S phase). The tumor specimens were fixed with 70 per cent ethanol, embedded in paraffin, sectioned and stained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 12 publications
4
13
0
Order By: Relevance
“…The probability of being diagnosed with a substantial cancer in a man's lifetime is 8% and 3% will eventually die from it. Therefore, there is the overriding dilemma as to which cancers should be diagnosed and which ones should be treated.Experimental studies and animal models have shown that prostate cancer has a slow growth rate when com pared to other tumors [5], On the basis of indirect evi dence from volumes of incidental carcinomas in an au topsy series, it has been proposed that prostate cancer fol lows a simple exponential growth curve with a constant long doubling time throughout its entire natural history [2], However, these determinations fail to reveal whether there is prognostic predictability in the histologic evolu tion of cancer with time. They are based on morphologic evaluation at a single point in time.…”
mentioning
confidence: 99%
“…The probability of being diagnosed with a substantial cancer in a man's lifetime is 8% and 3% will eventually die from it. Therefore, there is the overriding dilemma as to which cancers should be diagnosed and which ones should be treated.Experimental studies and animal models have shown that prostate cancer has a slow growth rate when com pared to other tumors [5], On the basis of indirect evi dence from volumes of incidental carcinomas in an au topsy series, it has been proposed that prostate cancer fol lows a simple exponential growth curve with a constant long doubling time throughout its entire natural history [2], However, these determinations fail to reveal whether there is prognostic predictability in the histologic evolu tion of cancer with time. They are based on morphologic evaluation at a single point in time.…”
mentioning
confidence: 99%
“…As shown in the study with BrdU immunostaining [4], there was a significant difference in the PCNA index according to the glandular pattern of prostatic carcinoma. The proliferative activity of solid carcinomas was significantly higher than that of separate gland carcinomas and trabecular/fused gland carcinomas.…”
Section: Discussionmentioning
confidence: 65%
“…It has been demonstrated that the proliferative activity of tumors is correlated with metastatic potential, recur rence and overall prognosis [1], Studies regarding the pro liferative activity of such tumors have up to now been mainly performed using flowcytometry [2], the incorpora tion of radiolabeled materials such as tritiated thymidine [3] and bromodeoxyuridine (BrdU) [4], and monoclonal antibodies such as Ki-67 [5,6]. Immunohistochemical methods of assessing cell proliferation have advantages and incubated at 4°C overnight.…”
Section: Introductionmentioning
confidence: 99%
“…Proliferation activity in prostate cancer has been assessed by immunohistochemistry using Ki-67 monoclonal antibody (16,17), PCNA (18) and tritium[ 3 H]-thymidine or bromodeoxyuridine labeling (19,20). Some studies demonstrated progressively rising levels of proliferative index (PI) values from PIN to invasive and metastatic carcinoma, illustrating the cancer progression (19,20). The mean PI values have been shown to range from 1.7 to 17.6% indicating low cell turnover consistent with a natural slow disease progression.…”
Section: Discussionmentioning
confidence: 99%